Synthesis of concentric circular antenna array for reducing the sidelobe level by employing sine cosine optimization algorithm - Thadikamalla, Nageswar Rao; Amara, Prakasa Rao (International journal of numerical modelling, 2024)
The sine cosine algorithm (SCA), a meta‐heuristic optimization method, is used in this study to provide a precise linear and elliptical antenna array design for synthesizing the ideal far‐field radiation pattern in the fifth‐generation (5G) communication spectrum. The wireless communication system will undergo dramatic changes thanks to the forthcoming 5G technology, which offers exceptionally high data rates, increased capacity, reduced latency, and outstanding service quality. The most important component of 5G communications is an accurate antenna array design for an optimum far‐field radiation pattern synthesis with a suppressed sidelobe level (SLL) value and half power beam width (HPBW). While long‐distance communication necessitates a low HPBW, the entire side lobe area needs a suppressed SLL to prevent interference. The SCA is used in this case to the optimal feeding currents applied to each array member in the design examples of the concentric circular antenna arrays (CCAA) discussed in this article. It shows the litheness and attainment of the propound algorithm named SCA, chosen CCAAs with three rings and varying amounts of components or antenna array sets those are stated as follows: Set I (4, 6, 8 elements), Set II (8, 10, 12 elements), Set III (6, 12, 18 elements), Set IV (8, 14, 20 elements) with and without the center element are amalgamate. Apply the PSO, Jaya, and SCA optimization algorithms for all four Sets of antenna arrays and compare the attained results; the SLL values achieved by the SCA technique are contrasted with those of other current optimization techniques. The outcomes of all examinations reveal that the SCA algorithm achieved a superior SLL reduction over other optimization techniques.